2015
DOI: 10.1093/ehjci/jev204
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reproducibility of novel echocardiographic three-dimensional automated software for the assessment of the aortic root in candidates for thanscatheter aortic valve replacement

Abstract: AimsA specialized three-dimensional transoesophageal echocardiography (3D-TOE) reconstruction tool has recently been introduced; the system automatically configures a geometric model of the aortic root from the images obtained by 3D-TOE and performs quantitative analysis of these structures. The aim of this study was to compare the measurements of the aortic annulus (AA) obtained by the new model to that obtained by 3D-TOE and multidetector computed tomography (MDCT) in candidates to transcatheter aortic valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Indeed, our group demonstrated that this automatic software allows modeling and quantification of the aortic root from 3D TEE data with high reproducibility in patients who underwent transcatheter aortic valve implantation. [13] Yet a direct evaluation through cardiac surgery confirmation would be needed to assess accuracy of the software measurements. In the present study, we aimed at providing a correct and complete assessment of the anatomy as well as of the dynamic MA geometry and displacement in the 3D space, showing annular characteristics and dynamics abnormal in both FMR and OMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our group demonstrated that this automatic software allows modeling and quantification of the aortic root from 3D TEE data with high reproducibility in patients who underwent transcatheter aortic valve implantation. [13] Yet a direct evaluation through cardiac surgery confirmation would be needed to assess accuracy of the software measurements. In the present study, we aimed at providing a correct and complete assessment of the anatomy as well as of the dynamic MA geometry and displacement in the 3D space, showing annular characteristics and dynamics abnormal in both FMR and OMR.…”
Section: Discussionmentioning
confidence: 99%
“…[1113] It allows fast and automatic quantitation of different MV components from 3D TEE images, with minimal human intervention, and seems to overcome many of the limitations of available software so far. Thus, the aim of the present study was to evaluate the feasibility of this new software to analyze MA dynamics in significant FMR and OMR and to correctly identify each of them, to provide additional noncurrently available parameters of MV function with possible clinical impact, and to evaluate reproducibility and time to perform the full analysis as a surrogate of its potential clinical applicability.…”
Section: Introductionmentioning
confidence: 99%
“…A promising version of reconstruction software that generates a geometric model of the aortic root from 3D TOE images and then performs quantitative analysis of these structures has been validated in a small pilot study against both standard 3D TOE and MDCT (33). There is also emerging computational modelling software that predicts the in vivo morphology of the implanted valve via finite element computer simulation.…”
Section: What Does the Future Hold?mentioning
confidence: 99%
“…Observational studies have been performed to compare 3D transesophageal echocardiography (3DTEE) with MDCT for annular sizing. This stems from the fact that contrast used in MDCT in pre‐TAVR aortic annulus sizing can induce kidney injury in as many as 7% to 10.5% of patients and the risk of this complication is much higher if the patient has pre‐existing renal impairment . Renal impairment in pre‐TAVR setting has been demonstrated as a pivotal predictor of morbidity and mortality …”
Section: Introductionmentioning
confidence: 99%